A hybridization technique for orphan legumes: development of an artificial interspecific pollination protocol for Crotalaria spp. Issue 2 (4th March 2021) - Wasonga, Mercy A.; Arunga, Esther E.; Neondo, Johnstone O.; Muli, Joshua K.; Kamau, Peter K.; Budambula, Nancy L. M.
ABSTRACT: Crotalaria brevidens: and C. ochroleuca commonly grown as vegetables have been extensively studied. However, information on breeding techniques is scanty. This study aimed to develop an artificial interspecific pollination protocol for two genotypes of Crotalaria with contrasting leaf and pod morphological features. The two are landraces that were previously collected from two counties in Kenya. The experimental design was a completely randomized design (CRD) in a greenhouse with C. ochroleuca as the female parent and C. brevidens as the male parent. Six-day-old flower buds of the female parent were emasculated. Pollen from a freshly opened flower was rubbed over the stigma of the emasculated flower. The pollinated stigma was inserted back into the keel petal and covered by the wing and standard petal. Data on success rate, pod, and seed production were subjected to analysis of variance. The developed artificial pollination method showed 75% success rate in the interspecies cross of C. ochroleuca and C. brevidens . Time of crossing did not significantly influence the success rate, pod, and seed production. The study demonstrated artificial interspecific pollination of Crotalaria by keel petal incision rubbing method. This protocol lays the foundation for genetic studies and improvement of Crotalaria spp.